Strategies for Teaching Arabic Phonetics in the Book “Iḍāʾāt Li-Muʿallimī Al-Lughah Al-ʿArabiyyah Li-Ghayr Al-Nāṭiqīn Bihā” by Abd Al-Rahman Al-Fawzan - Mulhendra Mulhendra (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2026)
Teaching Arabic pronunciation to non-native speakers requires systematic phonetic instruction to develop accurate articulation and communicative competence. However, practical phonetic training models based on established pedagogical references remain underexplored. This study aims to examine the concept and implementation of the dual sound training method (tadrībāt tsunā’iyyah) presented in Iḍāʾāt li-Muʿallimī al-Lughah al-ʿArabiyyah li-Ghayr al-Nāṭiqīn Bihā” by Abdurrahman Al-Fawzan. This research employs a qualitative descriptive approach using library research and content analysis. The findings reveal that the book proposes three progressive phonetic training stages: sound recognition, sound discrimination, and sound abstraction, which systematically enhance learners’ phonological awareness and pronunciation accuracy. The dual training method, particularly through minimal pair exercises, effectively improves learners’ ability to distinguish similar sounds. These findings suggest that the phonetic training model in Idhaat provides a practical and applicable framework for improving Arabic pronunciation among non-native learners.